THE IMPACT OF THE AUDITOR’S PERSONAL CHARACTERISTICS THROUGH DYSFUNCTIONAL AUDIT BEHAVIOUR ACCEPTANCE TOWARDS THE AUDIT QUALITY - Sambara, Elisha Jansen; Asnawi, Meinarni; Daat, Sylvia Christina (Fakultas Ekonomi, Universitas Cenderawasih, 2020)
The research aims to discover the impact of personal auditor’s characteristics, includingemployee’s performance, auditor burnout, professional commitment, turnover intention, selfesteem, locus of control, towards dysfunctional audit behavior acceptance, and its impact on thequality of audit through dysfunctional audit behavior. The technique employed in this research waspurposive sampling with 121 auditors at BPKP Province of Papua representative office and PapuaInspectorate Office as the size of the sample. However, there were only 94 used. StructuralEquation Model (SEM) with Partial Least Square (PLS) WrapPLS 6.0 method was also used astechnical analysis to test the variable’s impact. The research found that employee performance and self-esteem have no impact on the dysfunctionalaudit behavior, however auditor burnout, professional commitment, and external locus of controlhave significant and positive impacts on the dysfunctional audit behavior. Auditor burnout,turnover intention, and external locus of control have no impact on the quality of the audit,however, the employee’s performance, professional commitment, and self-esteem do have asignificant and positive impact on the quality of audit. All auditor’s characteristics have no impacton the quality of audit through dysfunctional audit behavior acceptance, another word, thedysfunctional audit behavior acceptance is not necessarily the intervening variable betweenauditor’s personal characteristic towards the quality of audit.